Oral parasites and Its Associated with the Population Residency and Some Physiological Disorders Among Population in Erbil City. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:The parasitic infection may be caused by the parasites Trichomonas tenax and Entamoeba gingivalis, which were included in this investigation. This studys goal is to estimation the incidence the parasites in patients' oral cavities with associated of some factors like residency, dental caries and diabetics in Erbil, Iraq.Materials and Methods:The current study comprised 354 patients in total. A questionnaire recorded residency (urban and Rural), dental caries and diabetics. Calculi samples were taken by use of a sterile curette and were placed in sterile collection vials, each containing 1 ml of sterile normal saline solution. Saliva samples of the patients were collected in sterile vials, then dilution was done by addition of 1 ml of sterile saline solution to each vial. Then each vial was labeled by patient’s number, name and date of collection. The purpose of collection the calculi and saliva to search about the parasites in the oral cavity. Results:The higher infection ratio of E. gingivalis in the rural regions in comparison with that of urban areas (91.7% and 89% respectively), and the results discovered that the higher positive rate of E. gingivalis (93.3%) was observed among those with dental caries and it was encountered in (86.8%)of subjects free from dental caries, regarding diabetes, diabetes and the presence of E. gingivaliswere shown to have a statistically significant connection (97.1%) and (35.7%) infection rates of E. gingivalis among diabetics and non-diabetic participitants respectively. While T. tenax was more common in individuals with non-diabetes (12.2%) compare to the diabetics (9.5%), but no relation was found.Conclusion:Infection with these parasites is relatively prevalent in people with dental caries, diabetics, and the persons' environment. It appears that continuation of advices are important in regulator of parasitic infection in Kurdistan Region of Iraq.